Peran UMKM Kembang Goyang Terhadap Peningkatan Pendapatan Masyarakat Desa Rasabou Kecamatan Bolo Kabupaten Bima - Taufik Hidayat; Muh. Syahru Ramadhan; Lilis Marlina (CV. Creative Tugu Pena, 2025)
This study aims to examine the role of the Kembang Goyang micro, small, and medium enterprise (MSME) in enhancing community income in Rasabou Village, Bolo District, Bima Regency. This MSME was selected due to its significant growth compared to similar businesses and its tangible contribution to job creation and economic empowerment, particularly for women. The research employed a qualitative case study approach, with data collected through in-depth interviews, observations, and documentation. The findings reveal that Kembang Goyang MSME plays a strategic role in increasing household income, generating employment opportunities, and strengthening family economic resilience. Several factors support its success, including independent capital, stable market demand, a flexible daily wage system, social-relation-based marketing strategies, and strong entrepreneurial motivation. Nevertheless, the enterprise faces challenges such as low-quality packaging, limited digitalization, restricted market access, and the absence of external support from government or development agencies. This research contributes to the literature on community-based MSMEs by highlighting how locally rooted enterprises can serve as catalysts for women’s empowerment, household economic resilience, and grassroots employment. The study also provides practical insights for policymakers and stakeholders to design synergistic support systems that enhance the sustainability and scalability of MSMEs leveraging local potential.